CCN1 stimulated the osteoblasts via PTEN/AKT/GSK3β/cyclinD1 signal pathway in Myeloma Bone Disease. (26th November 2019) - Yan, Siyang; Liu, Hui; Liu, Zhaoyun; Peng, Fengping; Jiang, Fengjuan; Li, Lijuan; Fu, Rong
Abstract: Backgrounds: Myeloma‐related bone disease (MBD) is a common complication of multiple myeloma (MM), which can both decrease life quality and influence the prognosis of the patients. We have found that CCN1 stimulated proliferation and differentiation of osteoblasts in MM in vitro and in vivo, while its mechanism still remains unknown. Method: Bone marrow mononuclear cells were collected from MM patients and differentiated into the osteoblasts. After co‐culture with CCN1 in vitro, the intracellular signaling antibody array and western blot were performed to explore the signaling pathway. Furthermore, GSK3 β inhibitor TWS119 was used to check the pathway of CCN1 might have on osteoblasts in vitro. Results: For the protein array kit, the expressions of GSK3 β, 4E‐BP1, and PTEN are decreased in CCN1 group. For western blots, the CCN1 group also has lower expression comparing to the control group in PTEN ( P = .031). Meanwhile p‐AKT and cyclinD1 levels have increased in the CCN1 group ( P = .002, P = .039). After adding TWS119 as another group, western blot was performed again to verify the pathway. For upstream proteins PTEN and p‐AKT, TWS119 group has higher expression level compared to that in CCN1 group ( P = .003, P = .001). And for downstream protein cyclinD1, TWS119 group also presented higher level than the control group ( P = .02). CCN1 could have almost the same effect on GSK3 β as the specific inhibitor TWS119 had. Conclusions: CCN1 can stimulate osteoblasts through PTEN/AKT/GSK3 β /cyclinD1 pathway in MBD, which has the potential to be a novel therapy of MBD. Abstract : CCN1 and GSK3 β inhibitor TWS119 had the same effect on decreasing the viability of GSK3 β . Control group was cultured only with medium, CCN1 group was cultured with CCN1 at concentration of 30 ng/mL and TWS119 group was cultured with TWS119 at concentration of 2 μmol/L. The three groups were all incubated for 72 hours. GAPDH and β ‐actin served as loading control. * P < .05; ** P < .01.